Fundamental uncertainty and unconventional monetary policy: an info-gap approach - Yakov Ben-Haim; Maria Demertzis; Jan Willem van den End (Bruegel, 2017)
This paper applies the info-gap approach to the unconventional monetary policy of the Eurosystem and so takes into account the fundamental uncertainty on inflation shocks and the transmission mechanism. The outcomes show that a more demanding monetary strategy, in terms of lower tolerance for output and inflation gaps, entails less robustness against uncertainty, particularly if financial variables are taken into account. Augmenting the Taylor rule with a financial variable leads to a smaller loss of robustness than taking into account the effect of financial imbalances on the economy. However, in some situations, the augmented model is more robust than the baseline model. A conclusion from our framework is that including financial imbalances in the monetary policy objective does not necessarily increase policy robustness, and may even decrease it.
Keywords: 330